5(x-4)+6x=3(1-x)

Simple and best practice solution for 5(x-4)+6x=3(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)+6x=3(1-x) equation:


Simplifying
5(x + -4) + 6x = 3(1 + -1x)

Reorder the terms:
5(-4 + x) + 6x = 3(1 + -1x)
(-4 * 5 + x * 5) + 6x = 3(1 + -1x)
(-20 + 5x) + 6x = 3(1 + -1x)

Combine like terms: 5x + 6x = 11x
-20 + 11x = 3(1 + -1x)
-20 + 11x = (1 * 3 + -1x * 3)
-20 + 11x = (3 + -3x)

Solving
-20 + 11x = 3 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-20 + 11x + 3x = 3 + -3x + 3x

Combine like terms: 11x + 3x = 14x
-20 + 14x = 3 + -3x + 3x

Combine like terms: -3x + 3x = 0
-20 + 14x = 3 + 0
-20 + 14x = 3

Add '20' to each side of the equation.
-20 + 20 + 14x = 3 + 20

Combine like terms: -20 + 20 = 0
0 + 14x = 3 + 20
14x = 3 + 20

Combine like terms: 3 + 20 = 23
14x = 23

Divide each side by '14'.
x = 1.642857143

Simplifying
x = 1.642857143

See similar equations:

| -9-3x=-5x+9 | | 1w-4=9-1w | | X+x=22+6 | | 28p=6p^2 | | .65X=9.10 | | 4-10k=34 | | x=4*60-160 | | 5+7(2x+11)+4x= | | 3x-6+8x=2x-3 | | W-4=9-w | | f(x)=-11x+3 | | 7x-7=4(2x-3) | | 12-12y-3(y+2)=4y+6-y | | x^3+40=13 | | 5e^9t=7e^8t | | 9+6=135 | | 2x+(-7+1x)=-1 | | 3x(x+2)=-18 | | -2(y+2)=3y | | 7s-8=64 | | y=17x^3 | | -14-8-6c=12-4c | | x=.25*150+40 | | 15-4(x+3)=19 | | 0.6h=13.032 | | 8s-8=65 | | Logx=.75 | | 5x-5+4x=-41 | | 3x+(x-5)=-11 | | 7x+2(0)=3 | | H(1)=-16t^2+96t+6 | | 4y-21-9y+35= |

Equations solver categories